(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Multi Level Inverter’s (MLI’s) has been considered as the primary choice for most of the industrial applications because of its reliability and high-power handling capability. In this paper, model predictive control has employed to guess the future values of load current by referring all the possible voltage vectors delivered by the inverter. Discrete-time model of the system is utilized to achieve the above-mentioned function. The voltage vector by which the quality function is minimized, is selected. Then the usage of switch state deduced that obtained by the selected voltage vector is used to control the next output voltage of the inverter. This model is easy to implement and it has the ability to overcome the drawbacks of conventional control techniques that are applied to the MLI’s. The result conveys that the model predictive control can effectively controls the load current and this system functions well.